The clinical effect of traditional chinese medicine on middle-aged women with Interstitial Cystitis: Protocol for a randomized controlled trial. Issue 14 (April 2020) - Liu, Yahong; Zhang, Pingan; Liu, Mengyu; Liu, Xiaohe; Liu, Ruijia; Yu, Xudong; Deng, Sheng; Si, Hongmei; Sun, Bei
Abstract: Introduction: Interstitial cystitis (IC), as a common disease in urology, is prolonged and repeated. IC has caused great harm to the patient's physical and psychological. Traditional Chinese medicine (TCM) is characterized by overall concepts and dialectical treatment. It provides clinicians with safer and more reliable alternatives in terms of clinical prescriptions and prepared medicines, and also improves the quality of life of patients with IC. Therefore, in this study, we will use the research method of randomized controlled trials to explore the effects of TCM combined with western medicine on renal function and urine metabolism on middle-aged women with IC. Methods/design: Use randomized controlled trials. According to the proposed diagnostic, inclusion, and exclusion criteria. Sixty patients with interstitial bladder inflammation that met the criteria were randomized into a treatment group and a control group of 30 cases each. The intervention group was treated with integrated traditional Chinese and western medicine. The control group was given conventional Western medicine treatment. The course of treatment is 8 weeks. Interstitial bladder inflammation symptoms score (ICS worker), problem score (worker CPI), pelvic pain and urinary urgency symptoms, and urodynamics were used as the evaluation criteria. Discussion: This trial may provide evidence regarding the clinical effectiveness, safety, and cost-effectiveness of TCM for patients with IC. Trial registration: ClinicalTrials.gov, ChiCTR2000029971, Registered on 17 February 2020